2021
DOI: 10.1002/fsn3.2328
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of physicochemical properties, amino acids, mineral elements, total phenolic compounds, and antioxidant capacity of Cuban fruit and rice wines

Abstract: Physicochemical characterization, amino acids contents, minerals composition, total phenolic compounds, and antioxidant capacity of Cuban wines from different raw materials were studied. The wines studied were grape wines, tropical fruit wines, and rice wines. Twenty‐one amino acids were identified and quantified, being Asp and Glu detected in all wines. The highest concentration of total amino acid content was found in wines elaborated from Cimarrona grape subjected to maceration with grape skins, while the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…As shown in Figure 3b , with the increase of aging time, the DPPH scavenging activity of the samples decreased gradually ( p < .01), but the scavenging rate of FRW was 13.05%–11.17% higher than that of RW. Previous studies found that the increase of total phenol in Cuban fruit wines was positively correlated with the increase of free radical scavenging activity (Núñez et al, 2021 ), which was consistent with the results of this study, indicating that the addition of chrysanthemum would promote the increase of free radical scavenging activity in FRW.…”
Section: Resultssupporting
confidence: 93%
“…As shown in Figure 3b , with the increase of aging time, the DPPH scavenging activity of the samples decreased gradually ( p < .01), but the scavenging rate of FRW was 13.05%–11.17% higher than that of RW. Previous studies found that the increase of total phenol in Cuban fruit wines was positively correlated with the increase of free radical scavenging activity (Núñez et al, 2021 ), which was consistent with the results of this study, indicating that the addition of chrysanthemum would promote the increase of free radical scavenging activity in FRW.…”
Section: Resultssupporting
confidence: 93%
“…5 (a) that LT1 had the highest total phenolic content, while LT2 has the lowest content. Moreover, the reason for differences in TPC between CRW fermented with Aspergillus oryzae and others fermented by wheat Qu may be because it was affected by strains (Núñez et al ., 2021). Rinaldi et al .…”
Section: Resultsmentioning
confidence: 99%
“…Amino acids are commonly present in fruit wines and play an important role in their taste [ 49 ]. Consistently with the present work, previous studies have detected aspartate, alanine, valine, tyrosine leucine, and isoleucine in KW [ 16 , 50 ].…”
Section: Discussionmentioning
confidence: 99%